Strategi Kerja Sama ASEAN Terhadap Penanganan Perubahan Iklim di Indonesia - Hichmah, Nurul; Santoso, Made Panji Teguh; Gustianti, Nurbani Adine (Peneliti.net, 2025)
Climate change has become a contemporary global issue that attracts the attention of the international community. Southeast Asia is one of the regions experiencing significant impacts of climate change. Indonesia, as a country located in this region, is experiencing rising temperatures, changes in rainfall patterns, and an increased risk of natural disasters. This research uses a qualitative approach to collect sources through literature studies through relevant sources and draws conclusions from the studies conducted. The results showed that ASEAN initiated various programs and cooperation frameworks, one of which was the formation of the ASEAN Working Group on Climate Change, as well as partnerships with Japan, South Korea, the United States, Norway, the United Kingdom, and Germany. This research provides insight into ASEAN's cooperation strategies in addressing climate change in Indonesia by analyzing ASEAN's cooperation strategies with various partner countries in addressing climate change challenges, identifying policies and initiative programs adopte,d and examining their impact on environmental policies in Indonesia.